Fatigue performance of hydraulic unit of high-pressure plunger pump. (December 2019) - Stepanov, Valentin; Kireev, Sergey; Korchagina, Marina; Kaderov, Haidar; Lebedev, Alexei
Abstract: The present paper considers a hydraulic unit of high-pressure plunger pump that relates to the main types of equipment for oil-and-gas well drilling, completing or repairing. The problem of fatigue breakdowns of hydraulic units of high-pressure plunger pumps is posed in the paper. According to the leading pump manufacturers, the main source of stress concentration in a valve casing of a pump is the edgings of crossing of cylindrical surfaces of seating fits, valves or plunger bores. The value of stresses in the concentrator zone was assessed, and values of safety coefficients of fatigue strength depending on geometric parameters of stress concentrators were compared. To solve the problem set by the leading manufacturers of pumps, the full-scale model of hydraulic unit was elaborated, stress condition and its effect on fatigue parameters of valve casing of hydraulic unit of oilfield high-pressure plunger pump were analyzed. The obtained calculation results quantitatively clarify the pattern of stress distribution in zones of stress concentration in a valve casing of hydraulic unit of a high-pressure plunger pump. Certain conclusions were made on how the parameters under consideration affect the values of fatigue stresses and on priority research directions for the problem under study.